An Investigation into the Effectiveness of Main Kolo (Sumbawa Traditional Games) in Teaching Speaking at 7th Grade of SMPN 1 Lopok - Hasrul Sani; Suparman Suparman (STKIP Yapis Dompu, 2023)
This research aims to investigate the effectiveness of using Main Kolo, Sumbawa Traditional Game from Sumbawa, in teaching speaking skills to 7th-grade students at SMPN 1 Lopok. The study is motivated by the need to explore innovative and culturally relevant approaches to English language teaching in the local context of Sumbawa. The participants of the study are 7th-grade students at SMPN 1 Lopok who receive English language instruction using Main Kolo as a teaching tool. The Result of this research are Pre-Test Score Control class, it can be seen that student’s ability in speaking skill. The mean score of control class pre test was 50.16. The minimum score of control class pre test was 44. The maximum score of control class pre test was 63. The standard deviation was 4.776, it can be seen that student’s ability in speaking skill. The mean score of experimental class pre test was 52.84. The minimum score of experimental class pre test was 44. The maximum score of experimental class pre test was 76. The standard deviation was 6.435. It can be seen that student’s ability in speaking skill. The mean score of control class post test was 69.00. The minimum score of control class post test was 64. The maximum score of control class pre test was 66. The standard deviation was 2.266. Then, it can be seen that student’s ability in speaking skill. The mean score of experimental class post test was 70.94. The minimum score of experimental class post test was 63. The maximum score of experimental class pre test was 88. The standard deviation was 4.864.